2007
DOI: 10.1007/s11144-007-4989-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wall carbon nanotubes supported ruthenium for glucose hydrogenation to sorbitol

Abstract: Multi-wall carbon nanotubes (MWNTs) supported ruthenium prepared with an impregnation method was used as catalyst in glucose hydrogenation to sorbitol. The effects of ruthenium loading, reaction time, temperature and initial hydrogen pressure on glucose hydrogenation were investigated. Compared with Raney Ni and ruthenium supported on Al 2 O 3 , SiO 2 , Ru/MWNTs showed higher catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…As shown in Fig. 5(e)-(h), the binding energy of Ru 3p 3/2 was 462.2-462.3 eV and the binding energy of Ru 3p 1/2 was 484.2-484.5 eV, which was in agreement with other studies on Ru/CNFs catalysts [18,19] and multi-wall carbon nanotubes (MWCNTs) supported Ru particles [16]. This result indicated that Ru particles existed in approximately identical chemical state in all the reduced Ru/CNFs catalysts, though Ru atoms existed in different forms when the as-prepared Ru/CNFs catalyst was calcined at different temperatures.…”
Section: September 2010supporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Fig. 5(e)-(h), the binding energy of Ru 3p 3/2 was 462.2-462.3 eV and the binding energy of Ru 3p 1/2 was 484.2-484.5 eV, which was in agreement with other studies on Ru/CNFs catalysts [18,19] and multi-wall carbon nanotubes (MWCNTs) supported Ru particles [16]. This result indicated that Ru particles existed in approximately identical chemical state in all the reduced Ru/CNFs catalysts, though Ru atoms existed in different forms when the as-prepared Ru/CNFs catalyst was calcined at different temperatures.…”
Section: September 2010supporting
confidence: 91%
“…was used to study the chemical state of the Ru particles because of the overlap of Ru 3d 3/2 peak with C 1s region [16,17]. As shown in Fig.…”
Section: September 2010mentioning
confidence: 99%
“…In other words, CNT was the most effective support for Ru catalyst for the conversion of cellulose into sorbitol. It is of interest to note that Pan et al [29] have reported that the CNT-supported Ru catalyst is much effective than the Al 2 O 3 -and SiO 2 -supported Ru and Raney Ni catalysts for the conversion of glucose to sorbitol. To clarify the role of CNT support in our case, we have carried out more detailed studies on Ru/CNT catalysts.…”
Section: Catalytic Conversion Of Cellulosementioning
confidence: 99%
“…It was established according to the analysis results ( Table 2) that ruthenium on the surface is in the form of the mixture of dioxide (Ru(IV)) with a different degree of hydration with the predominance of the latter. It is supposed that dioxide of ruthenium (Ru(IV)) is the oxidized ruthenium surface (Ru(0)) [39]. The absence of the ruthenate-anion should be noted in case Ru NPs are formed on the support with tertiary amine groups.…”
Section: Resultsmentioning
confidence: 99%